2021
DOI: 10.1097/bpo.0000000000001863
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic Glenohumeral Dislocation in Pediatric Patients Is Associated With a High Risk of Recurrent Instability

Abstract: Background: The natural history of traumatic glenohumeral dislocation is well-established in young adults, but it is less clear in pediatric patients. We aimed to determine the rate of recurrent instability and medium-term functional outcome following shoulder dislocation in patients aged 14 years or younger. Methods: All patients aged 14 years or younger who sustained a glenohumeral dislocation from 2008 to 2019 presenting to our regional health-board were identified. Patients who had subluxations associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…In this age group, patients are also at the highest risk of re-dislocation. In contrast, dislocations and subsequent recurrent instability are rare in the pre-pubertal population [5,[35][36][37]. In keeping with these findings, Old's systematic review of the literature prior to 2015 found that 14-18-year-old patients were 24 times more likely to experience re-dislocation than those aged 13 years and below, and those with a closed physis were 14 times more likely to dislocate than those with an open physis [18].…”
Section: Epidemiologymentioning
confidence: 93%
See 1 more Smart Citation
“…In this age group, patients are also at the highest risk of re-dislocation. In contrast, dislocations and subsequent recurrent instability are rare in the pre-pubertal population [5,[35][36][37]. In keeping with these findings, Old's systematic review of the literature prior to 2015 found that 14-18-year-old patients were 24 times more likely to experience re-dislocation than those aged 13 years and below, and those with a closed physis were 14 times more likely to dislocate than those with an open physis [18].…”
Section: Epidemiologymentioning
confidence: 93%
“…Some studies suggest that non-operative management may have greater success in skeletally immature patients [18,35]. This is possibly due to a lower rate of structural damage following a dislocation event, and the fact that these events are likely the result of a combination of type I, II, and III instability.…”
Section: Outcomes Of Non-operative Managementmentioning
confidence: 99%
“…In contrast, dislocations and subsequent recurrent instability are rare in the pre-pubertal population. [19][20][21][22] Table 1. Epidemiological studies on incidence of shoulder instability and recurrence.…”
Section: Epidemiologymentioning
confidence: 99%
“…Some studies suggest that non-operative management may have greater success in skeletally immature patients [20,23]. This is possibly due to lower rate of structural damage following a dislocation event, and that these events are likely the result of a combination of type I, II and III instability.…”
Section: Outcomes Of Non-operative Managementmentioning
confidence: 99%
“…Skeletal maturity was associated with recurrent instability (6 of 24 immature patients compared with 12 of 17 mature patients; p = 0.01). Twenty percent of patients with recurrent instability and a mean of 8 dislocations required surgical intervention 58 .…”
Section: Shouldermentioning
confidence: 99%